If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5r + -1)(6r + -3) = 0 Reorder the terms: (-1 + 5r)(6r + -3) = 0 Reorder the terms: (-1 + 5r)(-3 + 6r) = 0 Multiply (-1 + 5r) * (-3 + 6r) (-1(-3 + 6r) + 5r * (-3 + 6r)) = 0 ((-3 * -1 + 6r * -1) + 5r * (-3 + 6r)) = 0 ((3 + -6r) + 5r * (-3 + 6r)) = 0 (3 + -6r + (-3 * 5r + 6r * 5r)) = 0 (3 + -6r + (-15r + 30r2)) = 0 Combine like terms: -6r + -15r = -21r (3 + -21r + 30r2) = 0 Solving 3 + -21r + 30r2 = 0 Solving for variable 'r'. Factor out the Greatest Common Factor (GCF), '3'. 3(1 + -7r + 10r2) = 0 Factor a trinomial. 3((1 + -5r)(1 + -2r)) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(1 + -5r)' equal to zero and attempt to solve: Simplifying 1 + -5r = 0 Solving 1 + -5r = 0 Move all terms containing r to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -5r = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -5r = 0 + -1 -5r = 0 + -1 Combine like terms: 0 + -1 = -1 -5r = -1 Divide each side by '-5'. r = 0.2 Simplifying r = 0.2Subproblem 2
Set the factor '(1 + -2r)' equal to zero and attempt to solve: Simplifying 1 + -2r = 0 Solving 1 + -2r = 0 Move all terms containing r to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -2r = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -2r = 0 + -1 -2r = 0 + -1 Combine like terms: 0 + -1 = -1 -2r = -1 Divide each side by '-2'. r = 0.5 Simplifying r = 0.5Solution
r = {0.2, 0.5}
| 7x+9+5x=-3x+14 | | t+38=7t+8 | | 2y=x-7 | | 3x-5=11x-29 | | 8+27x+6-14x=5+10x+9+3x | | t-47=-35 | | 9p+13=3p-5 | | 3t-47=-35 | | y^2=x | | y(2+5)-13=64 | | x^2+4x+1= | | 9m+5=29-3m | | 92-t=37 | | 3.14*3.14+b^2=30 | | 101-7x=11x+19 | | 3*3*3+b^2=30 | | (4x-1)(7x+8)=0 | | 3*3*3+b^2=25 | | 3*3+b^2=25 | | 60=3t-13t | | 95-3x=3x+17 | | 5x-14=51 | | 2y-6=-5 | | 95-3x=3x | | 4x=8-(-16) | | -14-3=7-10x | | 2w-4w=-12 | | 2(p+1)=3(p-1) | | 9+b^2=25 | | y=-13 | | a^2+b^2=25 | | -6-5=-7+x |